1991
DOI: 10.1200/jco.1991.9.10.1757
|View full text |Cite
|
Sign up to set email alerts
|

Limb-sparing surgery without radiotherapy based on anatomic location of soft tissue sarcoma.

Abstract: From 1980 through 1986, 119 patients with soft tissue sarcomas of the extremities were referred to our tumor center either before surgery (n = 78) or immediately after incisional biopsy or marginal excision (n = 41). The tumors were classified according to anatomic location at admittance as subcutaneous (n = 40), intramuscular (n = 30), and extramuscular tumors (n = 49). Open biopsy was omitted in 75 of the 78 patients referred before surgery; the preoperative diagnosis was based on physical and radiographic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(55 citation statements)
references
References 13 publications
3
50
0
2
Order By: Relevance
“…13,[19][20][21] Khanfir et al 5 studied the role of adjuvant RT in 133 patients treated with wide excision and a negative microscopic margin. They showed that adjuvant RT improved local control exclusively in patients with a minimal resection (margin <1 cm).…”
Section: Discussionmentioning
confidence: 99%
“…13,[19][20][21] Khanfir et al 5 studied the role of adjuvant RT in 133 patients treated with wide excision and a negative microscopic margin. They showed that adjuvant RT improved local control exclusively in patients with a minimal resection (margin <1 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Mankin et al ( 1982Mankin et al ( , 1996 found that errors, complications, and changes in the course and outcome were 2-12 times greater when the biopsy was done outside, instead of in a treatment center. Furthermore, in some centers, especially in Scandinavia, many patients are treated without open biopsy; the diagnosis is based on findings from the physical examination, radiological investigations, and fine needle aspiration to avoid local tumor spread (see pages 54-59 and Rydholm et al 1991, Rydholm 1992. In the 1982 report by Mankin et al, one half of the sarcoma patients in the USA were referred only after open biopsy.…”
Section: Centralization Of Soft Tissue Sarcomamentioning
confidence: 99%
“…However, in Sweden radiotherapy is used to a lesser extent. Both low-grade and high-grade sarcomas which are subcutaneously localized or completely surrounded by a muscle fascia (intramuscular sarcoma) can be treated surgically without radiotherapy, and yet remain at low risk for local recurrence ( < lo%), with little functional loss (23). However, the fascia shall not have been opened by previous biopsy.…”
Section: Surgerymentioning
confidence: 99%
“…Several published studies of surgery and postoperative radiotherapy report local recurrence rates between 10% and 28% (8,23,(49)(50)(51)(52)(53)(54). The series from the MD Anderson Cancer Center is one of the first and largest, involving 300 patients (7).…”
Section: Rudiofherupy and Surgerymentioning
confidence: 99%
See 1 more Smart Citation